Aplikasi Virtual Punch Training Menggunakan Microsoft Xbox Kinect - Wanangsyah, Wira; Wurijanto, Tutut; Sutanto, Teguh (Jurnal JSIKA, 2014)
Â Â Microsoft released a sensor called Kinect, a gaming control functions as an alternative in which the user can move freely to use his body when interacting with virtual menu or playing games. One example of Kinect Sports : Boxing, the game is not including the measurement display of speed and power punches.Based on the existing problems then will be proposed for an application that can calculate the speed and power of a punch using Kinect sensor technology , Calculation of speed and power punches using a series of formulas to calculate the speed and kinetic energy . Then the value resulting from the calculation become performance parameters during training session , and then the value of the performance will be made by comparing each rank highest value that has been created in the previous exercise in order to found a new highest score .Based on the results of this research and by making use of Kinect technology that jab punch force can be measure from its velocity and energy , to then be used as an assessment of the exercise that has been carried out . But Kinect technology itself still has limited movement in the form of respite captured by the sensor and there is noise in the depth-sensor .Â